Vascular Effects of Histamine (Nigerian Journal of Physiological Sciences, 2021)
Summary: Four subtypes of receptors (H1, H2, H3 and H4) mediate the actions of histamine. In the vascular wall, the effects of histamine are mediated via H1 and H2 receptors and the actions are modulated by H3 receptor subtype located on presynaptic neurones. Alterations in vascular responses to histamine are associated with experimental as well as a human form of hypertension, suggesting a role for histanine in cardiovascular regulation.